The Transdisciplinary Research Approach : A Local to Global STRIDE - Vishakha Kutumbale; Kanhaiya Ahuja (Routledge India, 2025)
Academic research in higher education must innovate to remain relevant, accurate, and accessible. This volume examines various methodological trainings conducted under the University Grants Commission-STRIDE (Scheme for Trans-disciplinary Research for India's Developing Economy), India, showcasing transdisciplinary research approaches across diverse contexts. These approaches underscore the importance of innovation, complex problem-solving and knowledge integration.Through case studies, the book explores tools and methods for conducting transdisciplinary research, including Six Sigma training, the use of theatre, novel techniques for academic writing, and primary dataset-based research. These methodologies aim to produce high-quality research that transcends discipline-specific boundaries and offers practical societal applications. The volume delves into research across fields such as agriculture, urban development, education, sustainability, and entrepreneurship, among others.Rich in empirical data and research strategies, this book serves as a valuable resource for researchers in social sciences, economics, sustainable development, research methodology, sociology, public policy and politics.